Constructing Authoritarianism in J.S. Khairen’s Bungkam Suara: A Gramscian Literary Study - Sutardi Sutardi; Joko Slamet Prasetyo (Edulitics (Education, Literature, and Linguistics) Journal, 2025)
This study examines the construction of authoritarianism in J.S. Khairen’s Bungkam Suara through Antonio Gramsci’s theory of hegemony. Positioned within contemporary literary criticism and political fiction studies, the research investigates how the novel represents ideological domination, surveillance culture, and democratic paradoxes through literary discourse and narrative strategies. Employing a qualitative literary discourse analysis, the study analyzes characterization, dialogue, narrative atmosphere, and symbolic representations to identify hegemonic mechanisms embedded in the text. The findings reveal that authoritarianism functions as the dominant ideology in the novel through surveillance systems, political propaganda, and the normalization of obedience. Capitalism, feudalism, socialism, and humanism also emerge as competing ideological formations that shape the narrative conflict. Drawing upon international scholarship in literary criticism, discourse studies, and postcolonial political fiction, this article argues that Bungkam Suara constructs authoritarianism not merely through political themes but through literary discourse that disciplines public consciousness and regulates social behavior. The study contributes to English literary scholarship by positioning contemporary Indonesian political fiction within broader discussions of dystopian narrative, ideological discourse, and authoritarian democracy in global literature.